The long-term distribution of expected inflation in the euro area: what has changed since the great recession? - Jonas Dovern; Geoff Kenny (European Central Bank (ECB), 2017)
This paper analyses the distribution of long-term inflation expectations in the euro area using individual density forecasts from the ECB Survey of Professional Forecasters. We exploit the panel dimension in this dataset to examine whether this distribution became less stable following the Great Recession, subsequent sovereign debt crisis and period when the lower bound on nominal interest rates became binding. Our results suggest that the distribution did change along several dimensions. We document a small downward shift in mean long-run expectations toward the end of our sample although they remain aligned with the ECB definition of price stability. More notably, however, we identify a trend toward a more uncertain and negatively skewed distribution with higher tail risk. Another main finding is that key features of the distribution are influenced by macroeconomic news, including the ex post historical track record of the central bank.
Keywords: E31; E58; 330; density forecasts; ECB; euro area; inflation expectations